The Comparative Impact of Cash Transfers and a Psychotherapy Program on Psychological and Economic Well-being - Johannes Haushofer; Robert Mudida; Jeremy Shapiro (Research Institute of Industrial Economics (IFN), 2021)
We study the economic and psychological effects of a USD 1076 PPP unconditional cash transfer, a five-week psychotherapy program, and the combination of both interventions among 5,756 individuals in rural Kenya. One year after the interventions, cash transfer recipients had higher consumption, asset holdings, and revenue, as well as higher levels of psychological well-being than control households. In contrast, the psychotherapy program had no measurable effects on either psychological or economic outcomes, both for individuals with poor mental health at baseline and others. The effects of the combined treatment are similar to those of the cash transfer alone.
Keywords: C93; O12; D90; 330; Unconditional cash transfers; Psychotherapy; Randomized experiment